Synonymic notes in the genus Chlaenius Bonelli, 1810 (Coleoptera: Carabidae: Chlaeniini) - Kirschenhofer, Erich (Zootaxa, 2017)
In a study by Chanu & Swaminathan (2017) recently published in Zootaxa, two species of Chlaenius from Rajasthan (India) were described, which, however, turned out to be synonyms.